Ground reaction forces and temporal characteristics define cutting performance - Welinski, M. L.; Lee, L. N.; McBroom, B.; Mufarreh, B.; Gidley, L. (International Journal of Exercise Science, 2021)
Moderate angle cutting maneuvers (between 45º and 90º) are common and essential performance skills for success in multidirectional sports. Research addresses the injury risks of cutting but few studies have attempted to quantify the performance of the cut itself. PURPOSE: To identify any anthropometric, kinematic, and/or kinetic markers of a high-performance cut so they may be taught and lead to more effective training. METHODS: Ten college-aged male athletes (mass 73.97 ± 8.77kg, height 1.81 ± 0.07m) and ten non-athletes (mass 87.37 ± 13.93kg, height 1.85 ± 0.04m) completed five moderate angle cutting trials with a speed constraint of 4.03 m/s - 4.44 m/s through a 3 m in to and 3 m out of a 60° change in direction set-up. Kinetic and kinematic measurements were recorded through ground reaction forces and lower limb angles. RESULTS: A Bonferroni correction revealed that athletes spent significantly less time in the propulsion phase (52.0% ± 0.02%, p < 0.02) compared to non-athletes (55.4% ± 0.03%, p < 0.02). The propulsion phase was determined as the percentage of the contact phase the knee was extending (e.g. Green, et al, 2012). The athletes produced significantly greater instantaneous values of X GRF, Y GRF, and Z GRF during the propulsion phase (p < .05). CONCLUSION: Greater GRFs coupled with shorter propulsion phases by the athletes accounted for the lack of differences in the propulsion impulse between the two groups. Changing direction in a shorter time improves an athlete`s ability to evade an opponent, by decreasing the time an opponent has to react to a new direction.